ANALISA SISTEM UDARA PEMBAKARAN DAN GAS BUANG PADA BOILER CFB UNIT 3 DI PT. INDO RIDLATAMA POWER - Wildan Mukhollad Yasin; Rachmasari Pramita Wardhani (MECHA JURNAL TEKNIK MESIN, 2022)
The combustion air system in general is a system that functions as a medium for transporting coal to the boiler as well as adding oxygen for the combustion process and making turbolence. Tomaintain efficient combustion in the boiler, the air after combustion must be adjusted to the amount ofcoal that will be burned into the furnace. While the exhaust gas system is the output of the combustionprocess which is used to transfer hot gas from the rest of the combustion process to the water andsteam pipes and air heating elements, after which the exhaust gas is channeled into nature. Before theflue gas from combustion is disposed of directly into nature, it must first meet the quality standards ofthe Ministry of Environment and Forestry for gas emissions. Keywords—PLTU, Boiler, Combustion Air and Flue Gas System